Long-term mortality in obese subjects undergoing malabsorptive surgery (biliopancreatic diversion and biliointestinal bypass) versus medical treatment - Ceriani, Valerio; Sarro, Giuliano; Micheletto, Giancarlo; Giovanelli, Alessandro; Zakaria, Ahmed S.; Fanchini, Marco; Osio, Chiara; Nosari, Italo; Morabito, Alberto; Pontiroli, Antonio E. (International Journal of Obesity, 2019)
Background and aim Aim of this study was to analyze long-term mortality in obese patients receiving malabsorptive bariatric surgery (BS)[biliopancreatic diversion (BPD) and biliointestinal bypass (BIBP)] in comparison to medical treatment of obesity. Patients and methods Medical records of 1877 obese patients [body mass index (BMI) > 35 kg/m 2 , aged 18–65 years, undergoing BS ( n = 472, 111 with diabetes) or non-surgical medical treatment ( n = 1405, 385 with diabetes), during the period 1999–2008 (visit 1)] were collected; non-surgical patients were matched for age, sex, BMI, and blood pressure, and life status and causes of death were ascertained through December 2016. Survival was compared across surgery patients and non-surgical patients using Kaplan–Meier plots and Cox regression analyses. Results Observation period was 12.1 ± 3.41 years (mean ± SD). Compared to non-surgical patients, BS patients had reduced all-cause mortality (34/472 (7.2%) vs 181/1,405 (12.9%) patients, χ 2 = 11.25, p = 0.001; HR = 0.64, 95% C.I. 0.43–0.93, p = 0.019). Cardiovascular and cancer causes of death were significantly less frequent in surgery vs no-surgery (HR = 0.26, 95% C.I. 0.09–0.72, p = 0.003; HR = 0.21, 95% C.I. 0.09–0.45, p < 0.001, respectively). Conclusion Patients who have undergone BPD and BIBP have lower long-term all-cause, cardiovascular-caused and cancer-caused mortality compared to non-surgical medical weight-loss treatment patients. Malabsorptive bariatric surgery significantly reduces long-term mortality in severely obese patients.